Selective and sensitive determination of dihydroxybenzene isomers in water samples using functionalized copper nanoparticles modified graphite electrode. (2021) - Suresh Babu, R.; Prabhu, P.; Sriman Narayanan, S.
Abstract: A highly selective and sensitive electrochemical sensor for the determination of environmentally hazardous dihydroxybenzene isomers such as hydroquinone (HQ), catechol (CC) and resorcinol (RS) was fabricated by electrodeposition of Cu nanoparticles on polycysteine film deposited graphite electrode in room temperature ionic liquid medium as electrolyte. The electrochemical characteristics of the polycysteine functionalized copper nanoparticles (PCFCuNP) modified electrode was studied using cyclic voltammetry. The voltammetric response of dihydroxybenzene isomers at the modified electrode showed the current densities remarkably higher than the bare graphite electrode and occurred at a reduced overvoltage. For HQ, CC, RS the oxidation peak currents are linear to the concentrations at the range of 3.3 × 10 -6 − 1.3 × 10 -3 M, 1.6 × 10 -6 −1.3 × 10 -3 M and 3.3 × 10 -6 − 9.0 × 10 -3 M with the detection limits of 1.1 × 10 -6 M, 5.3 × 10 -7 M and 1.1 × 10 -6 M, respectively (S/N = 3). The stable and fast response during amperometric method shows the potential application of the PCFCuNP modified electrode for flow system analysis. The method was successfully examined for two different water samples with high selectivity and sensitivity.